Study on the wall backscatter factor in mobile X-ray in-situ calibration - Xu Yang; Luo Chen; Huang Yan; Jia Kebin; Liu Yuntao; Lin Min (Nuclear Technology and Radiation Protection)
This article focuses on the in-situ calibration of area radiation monitors by examining changes in backscatter factors. A mobile X-ray irradiation device was developed, and a reference radiation level was established. Using the Monte Carlo method, an in-situ calibration measurement model was created to study backscatter factors at different distances and radiation field conditions for radiation qualities ranging from N-60~N-200. The accuracy of the simulation was verified, with a relative deviation between simulation and experimental results not exceeding ±4.7 %. In addition, the variation of the backscatter factors with different chamber-wall distances and wall materials was simulated. Results indicate that backscatter factors for all materials decrease as the chamber-wall distance increases. For conventional concrete, the maximum backscatter factor within the studied energy range did not exceed 1.35. It is important to note that for heavy concrete and lead, the presence of K absorption edges can result in a sudden increase in scattered radiation.